Is Luke 16,16–18 of Baptist's Provenience? - Bammel, E. (Harvard theological review, 1958)
In 1928 Maurice Goguel declared that Luke 16,16–18 was ʻsans relation organique sensible, and thereby repeated the result of older German research. Now David Daube has been able to show a continuous chain of ideas in this passage and has thus confronted the exegesis with a new situation. Therefore the question of the historical place of the passage becomes urgent once more.